La expulsión del paraíso urbano: representaciones de la ciudad informal en el filme Hechos consumados (1986) - Lagos-Olivero, Claudio (Comunicación y Medios, 2018)
The paper establishes the representations of urban typology known as “informal city” that the film Hechos consumados proposes (1986). A methodological design that relates city and mass media is used, from a mediational perspective, by Martín Serrano (2004). Certain categories are defined that allow the observation of this kind of urban order, which emerge from a previous theoretical analysis on the Latin American “informal city”. This is an interdisciplinary research that could be interesting to those who have the urban phenomenon as object of study, or to those who do it from the point of view of representations that the cinema constructs, as mediational practices.